3D Printed Actuators: Reversibility, Relaxation, and Ratcheting - Zhao, Song Chuan; Maas, Mariska; Jansen, Kaspar; van Hecke, Martin (Advanced Functional Materials, 2019)
Additive manufacturing strives to combine any combination of materials into 3D functional structures and devices, ultimately opening up the possibility of 3D printed machines. It remains difficult to actuate such devices, thus limiting the scope of 3D printed machines to passive devices or necessitating the incorporation of external actuators that are manufactured differently. Here, 3D printed hybrid thermoplast/conducter bilayers are explored, which can be actuated by differential heating caused by externally controllable currents flowing through their conducting faces. The functionality of such actuators is uncovered and it is shown that they allow to 3D print, in one pass, simple flexible robotic structures that propel forward under step-wise applied voltages. Moreover, exploiting the thermoplasticity of the nonconducting plastic parts at elevated temperatures, it is shown that how strong driving leads to irreversible deformations—a form of 4D printing—which also enlarges the range of linear response of the actuators. Finally, it is shown that how to leverage such thermoplastic relaxations to accumulate plastic deformations and obtain very large deformations by alternatively driving both layers of a bilayer; this is called ratcheting. The strategy is scalable and widely applicable, and opens up a new approach to reversible actuation and irreversible 4D printing of arbitrary structures and machines.
CRIS-Team Scopus Importer:2019-11-05
Keywords: 3D printing; 4D printing; additive manufacturing; shape morphing